Demographic profiling of British Olympic equestrian athletes in the twenty-first century - Dumbell, L. C.; Rowe, L.; Douglas, J. L. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
Analyses of the determinants for participation in specific sports have been neglected and the use of demographic profiling in equestrian sports is limited. The aim of this research was to compare demographic profiles of British Olympic equestrian athletes, across and within disciplines, and suggest implications for the national federation`s micro-level athlete development strategy. Data were collected about all Team GB equestrian competitors over the last five Olympic Games. Equestrian sports are not organised by sex segregation, however no female showjumping competitors have represented Team GB in the twenty-first century. Competitors ranged in age over five decades and support the unusual early start-late specialisation paradigm, introduced by the national federation in 2007. Horse ownership is unusual amongst competitors, although it is more common amongst male athletes. The inter-athlete variation and inter-discipline variation these athletes show post challenges to the single development strategy currently in use.